2015
DOI: 10.1016/j.diagmicrobio.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Incubation time of Mycobacterium tuberculosis complex sputum cultures in BACTEC MGIT 960: 4weeks of negative culture is enough for physicians to consider alternative diagnoses

Abstract: We retrospectively analyzed time to detection of 3747 positive MGIT sputum cultures at a laboratory in a country with heavy burden of tuberculosis. Ninety-nine percent of diagnostic cultures turned positive within 28 days, suggesting that physicians may consider alternative diagnoses if sputum cultures remain negative after 4 weeks of incubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…Baseline TDG is also correlated to time to conversion ( Visser et al, 2012 ) and inversely related to transmissibility ( Khan et al, 2018 ). TDG in treatment-naïve subjects are, as expected, lower in smear positive and NAAT positive subjects ( Khan et al, 2018 ) with median values ranging between 5 ( Bisognin et al, 2020 ; Ma et al, 2020 ) and 23 days ( Boehme et al, 2011 ; Bark et al, 2012 ; Pfyffer and Wittwer, 2012 ; Tyrrell et al, 2012 ; Visser et al, 2012 ; Olaru et al, 2014 ; Ogwang et al, 2015 ; Diriba et al, 2017 ; Khan et al, 2018 ; Zhao et al, 2019 ). A few recent studies suggest that, in the majority of clinical samples, growth of MTB could be detected within 28 days of incubation ( Pfyffer and Wittwer, 2012 ; Ogwang et al, 2015 ).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Baseline TDG is also correlated to time to conversion ( Visser et al, 2012 ) and inversely related to transmissibility ( Khan et al, 2018 ). TDG in treatment-naïve subjects are, as expected, lower in smear positive and NAAT positive subjects ( Khan et al, 2018 ) with median values ranging between 5 ( Bisognin et al, 2020 ; Ma et al, 2020 ) and 23 days ( Boehme et al, 2011 ; Bark et al, 2012 ; Pfyffer and Wittwer, 2012 ; Tyrrell et al, 2012 ; Visser et al, 2012 ; Olaru et al, 2014 ; Ogwang et al, 2015 ; Diriba et al, 2017 ; Khan et al, 2018 ; Zhao et al, 2019 ). A few recent studies suggest that, in the majority of clinical samples, growth of MTB could be detected within 28 days of incubation ( Pfyffer and Wittwer, 2012 ; Ogwang et al, 2015 ).…”
Section: Introductionsupporting
confidence: 72%
“…TDG in treatment-naïve subjects are, as expected, lower in smear positive and NAAT positive subjects ( Khan et al, 2018 ) with median values ranging between 5 ( Bisognin et al, 2020 ; Ma et al, 2020 ) and 23 days ( Boehme et al, 2011 ; Bark et al, 2012 ; Pfyffer and Wittwer, 2012 ; Tyrrell et al, 2012 ; Visser et al, 2012 ; Olaru et al, 2014 ; Ogwang et al, 2015 ; Diriba et al, 2017 ; Khan et al, 2018 ; Zhao et al, 2019 ). A few recent studies suggest that, in the majority of clinical samples, growth of MTB could be detected within 28 days of incubation ( Pfyffer and Wittwer, 2012 ; Ogwang et al, 2015 ). A US multicentric study reported a median TDG of 14 days (using the Mycobacterium Growth Indicator Tube (MGIT) system, Becton Dickinson, Allschwil, Switzerland) with a 100% detection of all positive samples within 28 days, thus suggesting that there was no additional benefit of growing MTB on solid or liquid media for more than 5 weeks ( Tyrrell et al, 2012 ).…”
Section: Introductionsupporting
confidence: 72%
“…Early diagnosis and treatment are essential measures for effectively controlling the epidemic disease [ 1 ]. However, TB detection remains a major obstacle due to several drawbacks of the available diagnostic methods, such as tuberculin skin test [ 2 ], bacteriological culture (e.g., mycobacteria growth indicator tube) [ 3 ], sputum smear microscopy, radiographic methods [ 4 ], and biochemical and nucleic acid amplification methods [ 5 ], among them. To date, the number of diagnosis approaches for TB has increased as the disease continues to be a mayor public health problem worldwide, as a result of the severe threat of multidrug-resistant (MDR) tuberculosis, extensively drug resistant TB (XDR) [ 6 ] and alarming frequency of TB among immunocompromised co-infected patients (e.g., HIV/AIDS) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid diagnosis of TB is critical for initiating effective treatment and preventing its transmission in the community [1]. Recent advances in molecular methods have shortened the turnaround time for the identification of Mycobacterium tuberculosis (MTB); however, culture is still essential for phenotypic drug susceptibility testing and improving the case detection of smear negative patients [1, 2]. Due to the slow growth rate, conventional solid culture systems including Löwenstein-Jensen (LJ) slant or Middlebrook 7H11 agar plate always require 8 weeks of incubation before a negative result is reported, which cannot meet the criteria of clinical practice [3].…”
Section: Introductionmentioning
confidence: 99%
“…The culture is monitored with the oxygen-quenching fluorescent sensor technology every 60 minutes, which provides a satisfactory performance in a short laboratory turnaround time when compared with conventional method [2, 4, 5]. The BACTEC MGIT 960 is therefore widely considered as the gold standard for the diagnosis of TB [3].…”
Section: Introductionmentioning
confidence: 99%